Analisis Penyimpangan Prinsip Kesantunan Berbahasa Dalam Interaksi Belajar-Mengajar Siswa Kelas V SD Muhammadiyah Pakel Program Plus - Vina Deni Putria; Sugeng Riyanto (Universitas Ahmad Dahlan, 2020)
This study aims to describe the deviations of politeness language principles that occur in teaching-learning interactions and the causes of these deviations. Type of qualitative research. The main focus of this research is the utterances that occur in teaching-learning interactions to determine the form, type, and causes of deviations in politeness principles of language. Data collection techniques used are the SBLC technique (see free and capable conversation), note taking techniques and record techniques. The results showed that (1) the types of deviations in the language politeness principle that occurred in the interaction of teaching and learning of students in SD Muhammadiyah Pakel Plus Program consisted of deviations of wisdom maxims, deviations of generosity maxims, deviations of praise maxims, deviations of modesty maxims, deviations of agreement maxims, and deviations of wisdom maxims. maxim of agreement, (2) the cause of deviations in the politeness principle of language that occurs in the interaction of teaching and learning of students in SD Muhammadiyah Pakel Plus Program includes irregularities caused by speakers intentionally accusing the interlocutor, deliberately not speaking in context and criticizing directly with harsh words.